2017
DOI: 10.1037/mil0000195
|View full text |Cite
|
Sign up to set email alerts
|

American Military Veteran Entrepreneurs: A Comprehensive Profile of Demographic, Service History, and Psychosocial Characteristics

Abstract: American military veterans are nearly twice as likely to be self-employed compared to non-veterans, and are majority owners in nine percent of all businesses nationwide. Despite their contribution to the broader economy and the potential for training programs to cultivate and foster successful self-employment and veteran-lead entrepreneurial ventures, research on veteran entrepreneurs remains limited. In order to gain a better understanding of the potential strengths and vulnerabilities of veteran entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Efforts to support self-employment may help mitigate unemployment among veterans. Results from Heinz et al (74) demonstrated that veteran entrepreneurs experienced a higher number of traumas compared to non-entrepreneurs, but veterans entrepreneurs did not report higher levels of PTSD or other psychopathology. These results suggest that higher trait levels of optimism, extraversion, gratitude, curiosity (i.e., need for autonomy), and openness may contribute to resilience in veteran entrepreneurs.…”
Section: Self-employmentmentioning
confidence: 99%
“…Efforts to support self-employment may help mitigate unemployment among veterans. Results from Heinz et al (74) demonstrated that veteran entrepreneurs experienced a higher number of traumas compared to non-entrepreneurs, but veterans entrepreneurs did not report higher levels of PTSD or other psychopathology. These results suggest that higher trait levels of optimism, extraversion, gratitude, curiosity (i.e., need for autonomy), and openness may contribute to resilience in veteran entrepreneurs.…”
Section: Self-employmentmentioning
confidence: 99%
“…Learning effect A successful enterprise often provides other enterprises in the industrial cluster with labor division and cooperation opportunities in a complex environment, and take full advantage of entrepreneurial resources to establish new enterprises successfully and achieve economic and social profits (Ratna, 2018). Some researchers propose that the dependence of entrepreneurs on resources and personal characteristics has a great impact on the success of enterprises, and it also plays an important role in promoting the development and growth of science and technology (Heinz et al, 2017;Lv et al, 2021).…”
Section: Market Penetrationmentioning
confidence: 99%
“…While research on veteran self‐employment is quite limited, Heinz et al. (2017) report that veterans who are self‐employed tend to be older and more educated and to have had shorter military careers than veterans who are employees. This pattern of self‐employment rising with age, which is also seen in the general population (Fuchs, 1982; Zissimopoulos & Karoly, 2007), may reflect a desire among some workers to use self‐employment as a means of retiring gradually, particularly in the presence of hours constraints or in order to facilitate a change of occupation.…”
Section: Previous Literaturementioning
confidence: 99%